2014
DOI: 10.2340/00015555-2394
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 is Dysregulated in the Skin of Patients with Vitiligo and Inhibits Melanogenesis-associated Genes in Melanocytes and Keratinocytes

Abstract: Little is known about the functions of microRNAs (miRNAs) in skin pigmentation disorders. The aim of this study was to investigate the expression and potential role of miRNAs in vitiligo. Of 12 studied miRNAs with proven functions in cell proliferation, differentiation, immune responses and melanogenesis, miR-99b, miR-125b, miR-155 and miR-199a-3p were found to be increased and miR-145 was found to be decreased in the skin of patients with vitiligo. Combined pathway and target analysis revealed melanogenesis-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 59 publications
2
50
1
Order By: Relevance
“…As miR-146a/b have similar expression level in vivo in human and mouse skin, miR-146a/b together might have remarkably stronger influence than studies performed with miR-146a−/− mice demonstrate. On the other hand, the observation that the expression of miR-146a/b in normal skin and psoriatic lesions is 10-50-fold lower than that of the most highly expressed miR-203 and miR-125b further supports the therapeutic potential of miR-146a/b overexpression (Lovendorf et al , 2015; Sahmatova et al , 2016). …”
Section: Discussionmentioning
confidence: 87%
“…As miR-146a/b have similar expression level in vivo in human and mouse skin, miR-146a/b together might have remarkably stronger influence than studies performed with miR-146a−/− mice demonstrate. On the other hand, the observation that the expression of miR-146a/b in normal skin and psoriatic lesions is 10-50-fold lower than that of the most highly expressed miR-203 and miR-125b further supports the therapeutic potential of miR-146a/b overexpression (Lovendorf et al , 2015; Sahmatova et al , 2016). …”
Section: Discussionmentioning
confidence: 87%
“…Dysregulated miRNA expression is associated with the pathogenesis of various inflammatory skin disorders such as psoriasis, atopic dermatitis, and allergic contact dermatitis (Sonkoly E et al , 2008), and there is some evidence implicating miRNAs in vitiligo. Gene expression microarray studies have revealed aberrant miRNA expression in the skin and serum of patients with vitiligo (Mansuri et al , 2014, Shi et al , 2014, Shi et al , 2013), with upregulation of miR-224-3p, miR-4712-3p, and miR-3940-5p in peripheral blood mononuclear cells (Wang et al , 2015), miR-25 upregulated in serum (Shi et al , 2016) and miR-99b, miR-125-b, miR-155, and miR-199a-3p upregulated in the skin (Šahmatova et al , 2016) of vitiligo patients. Little is known, however, about the exact role of miRNAs, their targets, and their mechanism of action in the pathophysiology of vitiligo.…”
Section: Introductionmentioning
confidence: 99%
“…miR-202 inhibits tumor progression and (Farhana et al, 2015;Lin et al, 2016;Meng et al, 2016) affects the immune system (Fornari et al, 2015;Owen et al, 2015). miRNAs regulate levels of expression of target genes by controlling the signal pathways (Š ahmatova et al, 2016;Wang et al, 2016). Some target genes of miR-202 have a regulatory effect on coat color, and studies have shown that expression of the miR-202 target gene wnt5a is correlated with sensitivity to bio-and targeted therapies of melanoma (Tímár et al, 2006).…”
Section: Discussionmentioning
confidence: 97%